NEW HOSTS and DISTRIBUTION RECORDS FOR NEMATODE PARASITES of FRESHWATER FISHES FROM São Paulo STATE, BRAZIL. - Abdallah, Vanessa Doro [UNESP]; de Azevedo, Kozlowiski; Carvalho, Edmir Daniel [UNESP]; da Silva, Reinaldo Jose (My University, 2012)
A study on the nematode parasites of nine species of freshwater fishes from Peixe River São Paulo, State, Brazil. was conducted. Fish were collected between February 2010 and March 2011 and the following species were found: Procamallanus (Spirocamallanus) inopinatus and Contracaecum sp. (larvae) in Astyanax altiparanae; Contracaecum sp. (larvae), Dioctophyma renale (larvae), Philometroides caudata, P. (Spirocamallanus) inopinatus, P. (Spirocamallanus) neocaballeroi (larvae) and P. (Spirocamallanus) saofranciscensis in Acestrorhynchus lacustris; Contracaecum sp. (larvae), Guyanema sp., Hysterothylacium sp. (larvae) and Icthyouris sp. in Cyphocharax modestus; Contracaecum sp. (larvae), Cosmoxynemoides aguirrei and Pharyngodonidae gen. sp. in C. nagelii; Dioctophyma renale (larvae), Hysterothylacium sp. (larvae) and Rhabdochona sp. in Gymnotus sylvius; Capillariidae gen. sp. in Hoplosternum littorale; Cosmoxynema vianai, Guyanema sp., Ichthyouris sp. and Travnema travnema in Steindachnerina insculpta; Contracaecum sp. (larvae), Procamallanus (Spirocamallanus) rebecae (larvae) in Triportheus angulatus and Rhabdochona acuminata in Triportheus nematurus. This is first study of nematode parasites from the Peixe River, therefore all the species found are new geographical records and 19 are new host records.